BEHAVIOURAL AND PHYSIOLOGICAL STRESS RESPONSES TO TRANSPORTATION IN A GROUP OF PRZEWALSKI’S HORSES (EQUUS FERUS PRZEWALSKII) - S. N. Ji; L. L. Yang; X. F. Ge; B. J.Wang; J. Cao; D. F. Hu (Journal of Animal and Plant Sciences, 2013)
A variety of stimuli such as transportation can cause stress to animal. Stress is expressed differently by free-ranging, captive wildlife and domestic animals, and the response can be characteristic of the species. Via observation ofbehaviour and measurement of faecal glucocorticoid metabolites (FGM), our research focused on the capture and reintroduction of Przewalski’shorses (Equus ferus przewalskii). The results showed that: (1) compared to pre-transportation behavior, one stallion and 5 females moved significantly moreand significantly decreased the time spent standing, stand resting, and drinking. The stallion mark excretion decreased significantly; and other behaviors showed no significant change. (2) The average FGM for female horses rose significantly from 22 hr pre-transportation to 24 hr post-transportation; the average FGM of the stallion also rose at respective times, and then declined. Seventy-two hours following transportation, all values returned to their respective baseline levels. In light of these results, we advise that the animal should be attentively cared for that the day of and the day following transportation. The recovering period length of FGM levelwas more similar to domestic animals than to other wildlife, which might be caused by nearly one hundred years of captive breeding of these horses. We believe that our results could be the basic data set, which can be used to compare with future monitoring data. Stress response of the Przewalski’shorse to transportation, as an artificial stimulus, can be used as a monitoring rewildingprocess method, which is also an indicator of the ultimately"rewilding".
Keywords: behaviour; faecal glucocorticoid metabolites; Przewalski’shorse; stress response; transportation stimulus